Seeking Repeating Anthropogenic Seismic Sources: Implications for Seismic Velocity Monitoring at Fault Zones. Issue 1 (30th December 2022) - Sheng, Y.; Mordret, A.; Brenguier, F.; Boué, P.; Vernon, F.; Takeda, T.; Aoki, Y.; Taira, T.; Ben‐Zion, Y.
Abstract: Seismic velocities in rocks are highly sensitive to changes in permanent deformation and fluid content. The temporal variation of seismic velocity during the preparation phase of earthquakes has been well documented in laboratories but rarely observed in nature. It has been recently found that some anthropogenic, high‐frequency (>1 Hz) seismic sources are powerful enough to generate body waves that travel down to a few kilometers and can be used to monitor fault zones at seismogenic depth. Anthropogenic seismic sources typically have fixed spatial distribution and provide new perspectives for velocity monitoring. In this work, we propose a systematic workflow to seek such powerful seismic sources in a rapid and straightforward manner. We tackle the problem from a statistical point of view, considering that persistent, powerful seismic sources yield highly coherent correlation functions (CFs) between pairs of seismic sensors. The algorithm is tested in California and Japan. Multiple sites close to fault zones show high‐frequency CFs stable for an extended period of time. These findings have great potential for monitoring fault zones, including the San Jacinto Fault and the Ridgecrest area in Southern California, Napa in Northern California, and faults in central Japan. However, extra steps, such as beamforming or polarization analysis, are required to determine the dominant seismic sources and study the source characteristics, which are crucial to interpreting the velocity monitoring results. Train tremors identified by the present approach have been successfully used for seismic velocity monitoring of the San Jacinto Fault in previous studies. Plain Language Summary: Temporal variations of seismic velocities in the vicinity of fault zones are informative for understanding the earthquake preparation phase, but the lack of appropriate methodology and observations hinders actual applications. Human activities generate strong seismic energy that is suitable for monitoring velocity changes at depth. We design an algorithm to search for persistent anthropogenic seismic sources for fault‐zone velocity monitoring, and the workflow can be generalized to other applications. The feasibility of our algorithm is tested on three different data sets in California and Japan. We find stable sources close to several important fault zones that have hosted or have the potential to host large earthquakes. This study paves the way for future works related to fault‐zone velocity monitoring. Key Points: Repeating anthropogenic seismic sources are useful for seismic velocity monitoring We use the stability of correlation functions over time as a proxy to search for persistent seismic sources Case studies in California and Japan demonstrate the potential for fault zone monitoring